General treatment of the multimode Jahn-Teller effect: study of fullerene cations - Ramanantoanina, Harry; Zlatar, Matija; García-Fernández, Pablo; Daul, Claude; Gruden-Pavlovi, Maja (Physical chemistry chemical physics : PCCP, 2013)
A general model for the analysis of the Adiabatic Potential Energy Surfaces (APES) of the molecules that are subject to the multimode Jahn-Teller effect is presented. The method utilizes the information obtained by DFT calculations on a distorted stationary point on the APES. The essence of the model is to express the distortion along a model minimal energy path called Intrinsic Distortion Path (IDP), projecting the geometry of the system on the normal modes of the either high-symmetry (HS) or low symmetry (LS) nuclear configuration. This allows us to determine the significance of all of the involved normal modes along a relevant particular path of distortion, and the direct calculation of the vibronic coupling constants. The IDP analysis is illustrated by the discussion of the multimode H ⊗ (g + 2h) JT effect in fullerene cations (C 60 + ) giving a deep insight into the origin and the mechanism of vibronic coupling in fullerene based molecules. A general approach, fully non-empirical, to analyse the multimode distortion using multideterminantal-DFT and Intrinsic Distortion Path methods has been presented and illustrated on C 60 + .